AMP-Activated Protein Kinase Attenuates High Salt-Induced Activation of Epithelial Sodium Channels (ENaC) in Human Umbilical Vein Endothelial Cells. (22nd August 2016) - Zheng, Wei-Wan; Li, Xin-Yuan; Liu, Hui-Bin; Wang, Zi-Rui; Hu, Qing-Qing; Li, Yu-Xia; Song, Bin-Lin; Lou, Jie; Wang, Qiu-Shi; Ma, He-Ping; Zhang, Zhi-Ren
Abstract : Recent studies suggest that the epithelial sodium channel (ENaC) is expressed in the endothelial cells. To test whether high salt affects the NO production via regulation of endothelial ENaC, human umbilical vein endothelial cells (HUVECs) were incubated in solutions containing either normal or high sodium (additional 20 mM NaCl). Our data showed that high sodium treatment significantly increased α -, β -, and γ -ENaC expression levels in HUVECs. Using the cell-attached patch-clamp technique, we demonstrated that high sodium treatment significantly increased ENaC open probability (P O ). Moreover, nitric oxide synthase (eNOS) phosphorylation (Ser 1177) levels and NO production were significantly decreased by high sodium in HUVECs; the effects of high sodium on eNOS phosphorylation and NO production were inhibited by a specific ENaC blocker, amiloride. Our results showed that high sodium decreased AMP-activated kinase (AMPK) phosphorylation in endothelial cells. On the other hand, metformin, an AMPK activator, prevented high sodium-induced upregulation of ENaC expression andP O . Moreover, metformin prevented high salt-induced decrease in NO production and eNOS phosphorylation. These results suggest that high sodium stimulates ENaC activation by negatively modulating AMPK activity, thereby leading to reduction in eNOS activity and NO production in endothelial cells.